Surgical Management of a Rare Superficial Cutaneous Angiomyxoma in a Cow - Rani, R Uma; Jagatheesan, P N Richard; Sowbharenya, C; Arun, R; Arulanandam, K; Pazhanivel, N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A pluriparous, 16 year old,  Jersey crossbred cow was brought with the history of having a mass in the right flank region with increasing in size since six months. On clinical examination,  the cutaneous mass was a large, pedunculated,  painless,  firm, and ulcerated in the right lateral region of lower abdomen. Under xylazine sedation and 2% lignocaine local infiltration anaesthesia, the tumor mass surgically removed and it was confirmed as superficial cutaneous angiomyxoma on histopathological examination.
Keywords: Surgical Management; Rare Superficial